Involvement of CGRP‐RCP in the caveolin‐1/ERK1/2 signal pathway in the static pressure‐induced proliferation of vascular smooth muscle cells. Issue 10 (9th May 2018) - Guo, Feng; Yang, Li; Luo, Jingfei; Quan, Haiyan; Wang, Zhen; Peng, Hongyan; Hong, Chenliang; Li, Jie; Jiang, Zhisheng; Zhang, Liang; Qin, Xuping
Abstract : Previous study suggested that the receptor component protein (RCP), one of the components of calcitonin gene‐related peptide (CGRP) receptor, plays a multiple role in the cellular signal transduction. The study was designed to investigate whether or not the RCP involved in the regulation of caveolin‐1/extracellular signal‐regulated kinases‐1 and ‐2 (ERK1/2) signal pathway in the vascular smooth muscle cells (VSMCs) proliferation induced by static pressure. Mouse‐derived VSMCs line A10 (A10 VSMCs) was served as project in this experiment. Results showed that the A10 VSMCs viability and proliferating cell nuclear antigen (PCNA) expression which were increased by static pressure were inhibited by pretreatment of CGRP. In like manner, the expressions of the decreased‐caveolin‐1 and the increased‐phosphorylated ERK1/2 (p‐ERK1/2) induced by static pressure were significantly reversed by pretreatment of CGRP, respectively. Meanwhile, the expression of RCP was up‐regulated by the static pressure. Silence of RCP gene with the small interrupt RNA (siRNA) not only significantly increased A10 VSMC proliferation but also increased the expression of p‐ERK1/2 in response to static pressure. When treatment of A10 VSMCs with 120‐mmHg static pressure for different time, however, the protein band of caveolin‐1 and RCP was the least at time point of 10 min, but the p‐ERK1/2 expression was the most maximum. In conclusion, RCP maybe involved in the static pressure‐induced A10 VSMCs proliferation by regulation of caveolin‐1/ERK1/2 signal pathway. Abstract : In this study, we investigated whether or not RCP involved the mechanotransduction of static pressure, further, explored the essential effect of RCP on the caveolin‐1/ERK1/2 signal pathway in the static pressure‐induced A10 VSMCs proliferation.